Engineering challenges of ocean liming - Renforth, P; Jenkins, B; Kruger, T (Elsevier, 2013)
The relationship between the level of atmospheric CO₂ and the impacts of climate change are uncertain, but a safe concentration may be surpassed this century. Therefore, it is necessary to develop technologies that can accelerate CO₂ removal from the atmosphere. This paper explores the engineering challenges of a technology that manipulates the carbonate system in seawater by the addition of calcium oxide powder (CaO; lime), resulting in a net sequestration of atmospheric CO₂ into the ocean (ocean liming; OL). Every tonne of CO₂ sequestered requires between 1.4 and 1.7 tonnes of limestone to be crushed, calcined, and distributed. Approximately 1 tonne of CO₂ would be created from this activity, of which >80% is a high purity gas (pCO₂ >98%) amenable to geological storage. It is estimated that the thermal and electrical energy requirements for OL would be 0.6 to 5.6 GJ and 0.1 to 1.2 GJ per net tonne of CO₂ captured respectively. A preliminary economic assessment suggests that OL could cost approximately US$72-159 per tonne of CO₂. The additional CO₂ burden of OL makes it a poor alternative to point source mitigation. However, it may provide a means to mitigate some diffuse emissions and reduce atmospheric concentrations.